ANALYZING THE LEARNING STYLES OF SECOND-YEAR STUDENTS OF SMAN 6 SOPPENG IN LEARNING ENGLISH - Rahmah, Sakinah Aulia; Talib, Ahmad; Ariyani, Amra (Universitas Negeri Makassar, 2024)
This research aimed to determine the Learning Styles of Second-Year Students of SMAN 6 Soppeng and the Impact of Using the Learning Styles of Second-year Students of SMAN 6 Soppeng in Learning English. The method used in this research was a mixed method (QUAN-qual). The participants in this research were students of class XI Mia 1 SMAN 6 Soppeng. This class was selected as participants using purposive sampling techniques. The instruments used in this research were a questionnaire using Skala Likert techniques to determine the learning styles used by second-year students of SMA 6 Soppeng in learning English and interview questions to determine the impact of using learning styles by the second-year students on learning English. Based on the data results of the questionnaire as quantitative analysis, data obtained from as 59% of students are auditory learners, 27.9% are visual learners, and the least used learning style is kinesthetic learning style which only 13.11%, which means students in 11th grade of SMAN 6 Soppeng predominantly use auditory learning styles. As for the impact of learning styles experienced by students, they had experienced both of positive and negative impact of using learning styles in learning English.